The generation gap in endocrine disruption: can the integrated fish endocrine disruptor test (iFEDT) bridge the gap by assessing intergenerational effects of thyroid hormone system disruption? - Fagundes, Teresa; Pannetier, Pauline; Gölz, Lisa; Behnstedt, Laura; Morthorst, Jane; Vergauwen, Lucia; Knapen, Dries; Holbech, Henrik; Braunbeck, Thomas; Baumann, Lisa (Aquatic toxicology, 2024)
Thyroid hormones (THs) act early in ontogenesis, even prior to the differentiation of thyrocytes. Maternal transfer of THs is therefore known to play an essential role in early development. Current OECD test guidelines for the assessment of TH system disruption (THSD) do not address inter- or transgenerational effects. The integrated fish endocrine disruptor test (iFEDT), a test combining parental and developmental exposure of filial fish, may fill this gap. We tested the ability of the iFEDT to detect intergenerational effects in zebrafish (Danio rerio): Parental fish were exposed to propylthiouracil (PTU), an inhibitor of TH synthesis, or not exposed. The offspring was submitted to a crossed experimental design to obtain four exposure scenarios: (1) no exposure at all, (2) parental exposure only, (3) embryonic exposure only, and (4) combined parental and embryonic exposure. Swim bladder inflation, visual motor response (VMR) and gene expression of the progeny were analysed. Parental, but not embryonic PTU exposure reduced the size of the swim bladder of 5 d old embryos, indicating the existence of intergenerational effects. The VMR test produced opposite responses in 4.5 d old embryos exposed to PTU vs. embryos derived from exposed parents. Embryonic exposure, but not parental exposure increased gene expression of thyroperoxidase, the target of PTU, most likely due to a compensatory mechanism. The gene expression of pde-6 h (phosphodiesterase) was reduced by embryonic, but not parental exposure, suggesting downregulation of phototransduction pathways. Hence, adverse effects on swim bladder inflation appear more sensitive to parental than embryonic exposure and the iFEDT represents an improvement in the testing strategy for THSD.
Online verfügbar: 21. Mai 2024, Artikelversion: 1. Juni 2024
Gesehen am 25.11.2024